2018
DOI: 10.1080/2162402x.2018.1537693
|View full text |Cite
|
Sign up to set email alerts
|

Immunological differences between colorectal cancer and normal mucosa uncover a prognostically relevant immune cell profile

Abstract: T cells in colorectal cancer (CRC) are associated with improved survival. However, checkpoint immunotherapies antagonizing the suppression of these cells are ineffective in the great majority of patients. To better understand the immune cell regulation in CRC, we compared tumor-associated T lymphocytes and macrophages to the immune cell infiltrate of normal mucosa. Human colorectal tumor specimen and tumor-distant normal mucosa tissues of the same patients were collected. Phenotypes and functionality of tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 67 publications
2
31
0
Order By: Relevance
“…Tregs are involved inter alia in the suppression of inflammation mediated by effector T cells by several mechanisms including the release of TGF-β and IL-10 (44). In CRC, the average amount of Tregs was found to be increased in the blood of patients relative to healthy volunteers, and in the tumor relative to the adjacent non-tumor tissue (45,46). Moreover, several studies demonstrated that Tregs derived from both blood and tumor of CRC patients were able to suppress the proliferation of autologous CD4 and CD8 T cells (47,48), and that the frequency of Tregs was negatively correlated with the expression of IFN-γ and IL-2 in the tumors (49).…”
Section: Immune Players Associated With Poor Prognosismentioning
confidence: 99%
“…Tregs are involved inter alia in the suppression of inflammation mediated by effector T cells by several mechanisms including the release of TGF-β and IL-10 (44). In CRC, the average amount of Tregs was found to be increased in the blood of patients relative to healthy volunteers, and in the tumor relative to the adjacent non-tumor tissue (45,46). Moreover, several studies demonstrated that Tregs derived from both blood and tumor of CRC patients were able to suppress the proliferation of autologous CD4 and CD8 T cells (47,48), and that the frequency of Tregs was negatively correlated with the expression of IFN-γ and IL-2 in the tumors (49).…”
Section: Immune Players Associated With Poor Prognosismentioning
confidence: 99%
“…In contrast, autoimmune diseases and cancer are frequently associated with reduced neutrophil apoptosis 45 . Many solid tumors including colorectal cancer, lung cancer and breast cancer are characterized by a high neutrophil infiltration [46][47][48] . However, its predictive value differs between cancer types 8 .…”
Section: Neutrophil Cell Death In Disease Apoptosismentioning
confidence: 99%
“…Several studies demonstrated that Tregs negatively correlated with prognosis in CRC 47,48 . Interestingly, Tregs may suppress the proliferation of immunoreactive T cells, such as CD8T cell 49 .…”
Section: Discussionmentioning
confidence: 99%